Workshop Merancang Modul Ajar dengan Pendekatan Pembelajaran Mendalam Menggunakan AI pada Guru IPA SMP Kota Parepare - Setiawati, Henny; Isbatullah, Muhammad; Rifaat, Muhammad; Ashyfah, Ummu; Wahyudi Mursidin; Narsan, Zhalfariani (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This activity aims to improve the understanding of junior high school science teachers in Parepare City towards the immersive learning approach using artificial intelligence (AI). This activity involved 35 teachers who are members of the MGMP IPA. Data were collected through questionnaires and interviews to measure teachers' perceptions of immersive learning and their level of satisfaction with the workshop held. The results of the questionnaire showed that the majority of teachers understood the concept of immersive learning, although some still had difficulty in designing and managing time in its implementation. In addition, most participants expressed high satisfaction with the materials, delivery methods, and benefits obtained from the workshop. Thus, this activity made a positive contribution to improving teacher readiness in implementing AI-based immersive learning in the classroom. The recommendation from this study is the need for further training and the development of more comprehensive learning resources to support the implementation of immersive learning at the junior high school level.